The Role of Multichannel Marketing in Customer Retention and Loyalty: Study in Emerald Bank Customer in Indonesia - Ambarwati Ambarwati; Djumilah Zain Hadiwidjojo; Achmad Sudiro; Fatchur Rohman (APMBA (Asia Pacific Management and Business Application), 2014)
Attention on the relationship between customer retention, customer loyalty, and customer satisfaction that serves as "seed" of customer loyalty highlight the important factors for multichannel management. With the growing trends of people in investing their money in bank for securities need to be responded by the marketing department to create better marketing strategies. The purpose of this study is to examine and explain the effect of a multichannel bank on emerald customers retention   in one of the largest SOE bank in Indonesia, in the city of Surabaya, BNI (Bank Negara Indonesia) toward customer  satisfaction, loyalty and customer  retention. This study develops the theory  of  mix marketing by using multichannel  as one of the elements that can increase customer retention   using satisfaction mediation and customer loyalty. Mechanical determination of sample units in this study is a  purposive sampling, of 89 respondents. Generalized Structured Component Analysis (GSCA) was applied to test the hypotheses. The results of this study indicate that direct multichannel not  significantly effect the customer retention. Customer satisfaction can not be a perfect mediation  and the customer loyalty can be a perfect mediation in the relationship between multichannel and customer retention. This study contributes to the banking industry in applying the concept of the mix marketing.